Analisis Biaya Produksi Dengan Pendekatan Theory Of Constraint Untuk Meningkatkan Laba (Studi pada PG. Krebet Baru Malang) - Moestika Setyaningrum, Rina; Fauzan Hamidy, Muhammad (Jurnal Riset Ekonomi dan Bisnis, 2008)
Phenomenon produce of sand sugar in Indonesia increasingly unable to fulfill requirement, so that sugar import inescapable. Tendency of consumer to buy cheaper sugar import will have an effect on to continuity of sugar industry in Indonesia in the future. For that’s sugar mill Krebet Baru is challenged to be able to always stays and even to compete with the product increase. Obsolescence factor of factory machines happened at approximant 90% sugar mill in Indonesia. Approach of Theory of Constraint can increase profit by the way of minimization of production cost. Data analysis in this research applies approach of theory of constraint done through phases, that is : identifies banding constraint, determines exploiting that is most efficient, manages stream produce and calculation throughput. Authenticity of data is done with credibility test, member check and discussion. Result of analysis with applying of TOC in identifying and manages production constraint, can be made consideration to increase throughput and profit improvement of company. Ever greater of throughput yielded hence ever greater also company profit.Keywords: Theory Of Constraint, Production Cost, Throughput, Profit